The Future of Electric Cars in Australia: A case study of the Mitsubishi Outlander PHEV 2016-21 - Fullarton, Lex (Institute of Public Accountants, 2021)
This paper looks at a review of previous study, conducted in 2016, on a plug-in electric vehicle, and updates the data and findings of that previous paper. It finds that the up take of EVs in Australia is extremely slow however the last year has shown a significant increase in that transition to EV's.